2012
DOI: 10.1111/j.1467-8578.2012.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Reforms and challenges in the era of inclusive education: the case of China

Abstract: This article, written by Meng Deng of Beijing Normal University and Kim Fong Poon-McBrayer of the Hong Kong Institute of Education, reviews and analyses the reform of special education in China, the challenges confronting Chinese special education provisions, and how the Chinese inclusive education model, namely 'Learning in RegularClassrooms', has been shaped by the pragmatic needs aligning with the nation's economic and social developments. In an effort to provide wider school access, the current inclusive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 11 publications
3
40
0
Order By: Relevance
“…Or, it could be due to inefficient and ineffective prevention, provision, and treatment methods in the area of special education, resulting in high demand for special education provision. In this regard, prior research reported the need for further training for regular education teachers towards more inclusive education [18][19][20] (limitations of Learning in Regular Classrooms (LRC) [21][22][23][24]). Second, it is very interesting to see the number of total enrolment and graduates before and after the National Plan close to one another.…”
Section: Discussionmentioning
confidence: 99%
“…Or, it could be due to inefficient and ineffective prevention, provision, and treatment methods in the area of special education, resulting in high demand for special education provision. In this regard, prior research reported the need for further training for regular education teachers towards more inclusive education [18][19][20] (limitations of Learning in Regular Classrooms (LRC) [21][22][23][24]). Second, it is very interesting to see the number of total enrolment and graduates before and after the National Plan close to one another.…”
Section: Discussionmentioning
confidence: 99%
“…What these viewpoints do illustrate sharply, then, is that longstanding debate on school types, integration, independence, educators and access to learning continues within this group (for examples of the debates and issues, see e.g. Morgan, 1977;Hodgson, 1985a, b;Buultjens, 1986;Thomas & Jackson, 1986;Alan Dobbins & de la Mere, 1993;Stokes, 1993;Talbot & Farbey, 1997;Talbot, 2002;Pavey, Douglas, McLinden & McCall, 2003;Alghazo & Nagger Gaad, 2004;Rogers, 2007;Florian, 2008;Hess, 2010;Deng & Poon-McBrayer, 2012;Lee & Low, 2014).…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…These types of programmes would allow for the training of qualified inclusive education teachers. These programmes have not existed given that most of the current training programmes are short term and focus on the immediate needs of personnel (Deng and Poon-McBrayer 2012). In addition, the ITCQ factors and related items can serve as quality attributes of the professional standards and evaluation indicators for inclusive education training programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Villa and Thousand 2000;Westwood 2001;Rose 2011). The most challenging issue confronting Chinese inclusive teachers is that they lack expertise on how to differentiate instruction and handle behavioural problems of students with SEN (Feng 2010;Deng and Poon-McBrayer 2012). The second factor contains three items, and measures if teachers are able to communicate and cooperate effectively with various stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation